2003
DOI: 10.1046/j.1365-2656.2003.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of spawning age distribution on salmon persistence in fluctuating environments

Abstract: Summary 1.Understanding the role endogenous vs. exogenous forces play in determining the dynamics and abundance of natural populations has important implications for their conservation. 2. Changes in environmental conditions often have different effects on closely related species. For instance, recent studies show that a physical shift in ocean conditions in the mid-1970s in the California current have reduced coho salmon ( Oncorhynchus kisutsch ) populations, but not chinook salmon ( O. tshawytscha ).3. An im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…This result is mathematically similar to that of Gurney and Middleton (1996), who demonstrated that iteroparous organisms adopting an earlier onset of maturation become more advantageous under a stochastic environment. The present result is, furthermore, consistent with that of Hill et al (2003), which demonstrated that, under a stochastic environment, individuals with an indeterminate semelparous life-history strategy become more persistent than those with a determinate semelparous life-history strategy.…”
Section: Discussionsupporting
confidence: 91%
“…This result is mathematically similar to that of Gurney and Middleton (1996), who demonstrated that iteroparous organisms adopting an earlier onset of maturation become more advantageous under a stochastic environment. The present result is, furthermore, consistent with that of Hill et al (2003), which demonstrated that, under a stochastic environment, individuals with an indeterminate semelparous life-history strategy become more persistent than those with a determinate semelparous life-history strategy.…”
Section: Discussionsupporting
confidence: 91%
“…, 2001; MacCracken, 2004; Karraker et al. , 2006; Tait & Diller, 2006) and survival (Sagar, Olson & Schmitz, 2007 estimated D. tenebrosus annual survival), paired with the fact that anadromous fishes have complex and varied life histories that involve both freshwater and marine environments (Weitkamp & Neely, 2002; Hill, Botsford & Hastings, 2003; Shea, Wolf & Mangel, 2006), suggests that any statement about “similar life requisites” for salmon and SAA is at best premature, and at worst inaccurate.…”
Section: Four Unsubstantiated Assumptionsmentioning
confidence: 99%
“…Furthermore, within a population, diverse life histories can contribute to stability . Using population models, Hill, Botsford & Hastings (2003) suggested that higher levels of diversity of Pacific salmon ocean ages can increase predicted persistence in the face of variable ocean survival. However, there remains an incomplete understanding of how diverse life-history traits within populations contribute to temporal stability of Pacific salmonids.…”
Section: Introductionmentioning
confidence: 99%